2016
DOI: 10.1097/dcr.0000000000000614
|View full text |Cite
|
Sign up to set email alerts
|

Should Immunomodulation Therapy Alter the Surgical Management in Patients With Rectovaginal Fistula and Crohn’s Disease?

Abstract: Despite a relatively low success rate (63%) in healing after surgical repair of a rectovaginal fistula, the recent use of immunomodulation therapy did not negatively impact healing. However, tissue interposition techniques had the highest success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Failure to heal after a direct repair with a flap necessitates more challenging subsequent surgery due to the presence of fibrosis, which makes local tissues unfit for a new repair . All types of local repair should be avoided in cases of acutely or chronically inflamed local tissue as well as when patients are contemporaneously medically treated .…”
Section: Discussionmentioning
confidence: 99%
“…Failure to heal after a direct repair with a flap necessitates more challenging subsequent surgery due to the presence of fibrosis, which makes local tissues unfit for a new repair . All types of local repair should be avoided in cases of acutely or chronically inflamed local tissue as well as when patients are contemporaneously medically treated .…”
Section: Discussionmentioning
confidence: 99%
“…RVFs related to CD are challenging for surgeons, and a very high propensity to recur is observed, with published rates ranging from 25% to 80% [ 7 , 21 , 22 ]. An optimal medical or surgical control of local and distant CD acute/subacute manifestations must be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…28 The long-term outcomes of temporary fecal diversion, including rates of attempted and successful restoration of bowel continuity and need for additional surgery such as In the setting of CD-related rectovaginal fistula, a recent series of 120 patients demonstrated that the use of fecal diversion did not affect healing, but tissue interposition techniques had the highest success rates. 32 In a further series of 51 patients with rectovaginal fistula, 60% of patients treated with preoperative fecal diversion healed, and 51% of patients treated with nondiverted repairs healed. 33 While anorectal stricture is often considered an indication for definitive ostomy formation, a recent series of 102 patients demonstrated stricture healing in 59% at a median follow-up period of 2.8 years with 19 patients requiring definitive ostomy.…”
Section: Ostomy Formation For Management Of Perianal Fistulating Diseasementioning
confidence: 93%